Racialization of City Spaces through Moral Monitoring in Rotterdam, The Netherlands - Long, Jennifer (Lidé města, 2022)
The city of Rotterdam has had some o f the s trictest policing and security policies in the Netherlands. In public spaces, enforcement tactics have included such practices as preventative searches, as well as fines for individuals for hanging around in groups of three or more. This article explores the tactics used to enforce certain behaviours in public spaces that racialize city spaces. Further the author examines how other local urban occupants reinforce the ethnic and racial hierarchy of belonging in the Netherlands. The author uses situational analysis and in-situ ethnographic interviews as methods to engage difficult-to access populations in situations of policing and security.